The right to design: merging boundaries - Trigueiros, Paula (2017)
Workshop realizado no âmbito do The “Right to Design” states that the benefits of well-designed products - being it functional, emotional or any other - should be available to anyone. We are calling talented, curious designers for a “hands on” workshop, to address two specific challenges and discuss some contradictions that emerge from labeling designs.